An investigation into the role of lesson study in developing teachers' mathematics content and pedagogical content knowledge - Kgothego, Naomi Ntsae (Rhodes University, Faculty of Education, Department of Education)
Results of international assessments conducted with South African learners, both in primary and secondary schools, suggest that South African learners underperform in mathematics (Spaull, 2013). While there are numerous explanations for this, one of the key explanations is that teachers are deemed to have inadequate knowledge of both mathematics content and pedagogy. Poor content and pedagogical knowledge are indications that teachers are not adequately trained to teach mathematics (Green, 2011). To improve teachers' content and pedagogical knowledge, well-planned and researched professional development programmes need to be put in place. Current professional development opportunities that centre on workshops are not working as they provide little opportunity for teachers to connect the workshop content to the contexts in which they teach. Through a collaboration between the Department of Basic Education (DBE) and Japan International Corporation Agency (JICA), the Lesson Study approach is being introduced to support teachers' professional development. This research seeks to research this approach within the context of Foundation Phase mathematics education. The research asks: How does Lesson Study contribute to the development of teachers' mathematics content and pedagogical content knowledge? Two sub-questions were developed to support the main question: "¢ What mathematics content knowledge do teachers develop as the engage in LS? "¢ What pedagogical content knowledge do teachers develop as they engage in LS? Using a qualitative interpretivist case study approach, I worked collaboratively with four Grade 1 teachers from two schools. Data was generated through observations, semi-structured interviews and document analysis as we engaged in the Lesson Study process. The Mathematics Knowledge for Teaching (Ball, Thames & Phelps, 2008) and the Knowledge Quartet (Rowland, Turner, Thwaites & Huckstep, 2009) frameworks were used as analytic and explanatory tools in this research. This study's findings showed that participation in the interactive cycles of Lesson Study developed the teachers' confidence, their pedagogical content knowledge and skills and provided them with the opportunity to collaborate and reflect on their knowledge. The study's findings suggest that lesson study can be used as a strategy for improving teacher professional development.
Keywords: Mathematics -- Study and teaching (Elementary) -- South Africa -- Bojanala Platinum District Municipality; Pedagogical content knowledge; Lesson planning -- South Africa -- Bojanala Platinum District Municipality; Mathematics teachers -- Training of -- South Africa -- Bojanala Platinum District Municipality; South Africa. Department of Basic Education; Kokusai KyoÌ„ryoku JigyoÌ„dan